Social Class Representation in Emily Brontë’s Wuthering Heights: A Marxist Descriptive Analysis - Ahmad Rizal Abdullah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study examines the representation of social class in Emily Brontë’s Wuthering Heights through the lens of Marxist literary criticism. While previous research has discussed themes such as class hierarchy, symbolic power, and economic determinism, limited attention has been given to how these dynamics are directly embedded in the novel’s dialogue and narrative interactions. To address this gap, this research analyzes twenty selected textual excerpts using key Marxist concepts, including class struggle, ideology, and material conditions. The study employs a qualitative descriptive approach, drawing on the works of Marx and Engels, Eagleton, and other theorists to interpret how language and character behavior reflect social positioning. The findings show that Wuthering Heights portrays a deeply stratified social environment in which identities, decisions, and conflicts are shaped by class-based power relations. Heathcliff’s marginalization, Catherine’s status-driven choices, and Hindley’s abusive dominance embody recurring patterns of oppression and resistance consistent with Marxist theory. The study concludes that Brontë’s novel not only dramatizes interpersonal tensions but also exposes the structural inequalities that govern them, offering a more nuanced understanding of how Victorian literature reflects and critiques social class. This research contributes to existing scholarship by providing a dialogue-centered, textually grounded analysis that clarifies the mechanisms of class representation more precisely than broader thematic studies.